Thermohydraulic characteristics of a micro plate heat exchanger operated with nanofluid considering different nanoparticle shapes. (October 2020) - Bahiraei, Mehdi; Monavari, Ali
Highlights: Hydrothermal attributes of a micro plate heat exchanger using the boehmite alumina nanofluid. Study is done for nanoparticle shapes of platelet, brick, cylinder, blade, and oblate spheroid. Platelet-shaped particles result in the maximum overall heat transfer coefficient and heat transfer duty. The nanofluid having the Os-shaped particles leads to the highest effectiveness. By elevating the Reynolds number, the pressure loss and effectiveness increase. Abstract: Improvement in thermal performance of plate heat exchangers is crucial, and nanoparticle shape can have significant effects on their efficiency in the case of using nanofluids as working fluid. In the current contribution, the thermal and hydraulic attributes of a microchannel plate heat exchanger, using the boehmite alumina nanofluid in the hot fluid side and the pure water in the cold fluid side, are analyzed. The finite volume method is employed in the simulations. This investigation is performed for five particle shapes (i.e., platelet, brick, cylinder, blade, and oblate spheroid) at inlet temperature of 90 °C and Reynolds number of 500 for the hot fluid side. In the cold fluid side, three inlet temperatures (i.e., 10, 20, and 30 °C) and three Reynolds numbers (i.e., 500, 1000, and 1500) are considered. The nanoparticle concentration is considered constant ( φ  = 1%) for all the particle shapes. The nanofluid having the platelet-shaped particles results in the maximum overall heat transfer coefficient ( U ) and heat transfer duty ( q ), followed by the suspensions containing the cylinder-, blade-, brick-, and Os-shaped particles, respectively. Moreover, the nanofluid having the Os-shaped particles leads to the highest effectiveness, followed by the suspensions with the brick-, blade-, cylinder-, and platelet-shaped nanoparticles, respectively. Additionally, by diminishing the inlet temperature of the cold water, the performance index and q enhance for all the nanoparticle shapes. Besides, by elevating the Reynolds number, the pressure loss, effectiveness, heat transfer rate, and U increase. The main novelty of this investigation is to evaluate the effects of nanoparticle shape on the thermohydraulic performance of nanofluids in the micro plate heat exchanger.